KAJIAN KOMPREHENSIF MENGENAI KESIAPAN KARYAWAN UNTUK BERUBAH: PERHATIAN PADA PERSEPSI KARYAWAN TERHADAP KONTEKS ORGANISASI DAN PROSES PERUBAHAN - Mariska Diona; Rayini Dahesihsari (MANASA, 2016)
In order to keep up with the dynamic development of its surroundings, organizations need improve and develop its internal process, including by changing the structure of the organization. To ensure the success of the change implementation, management of organization should pay attention on managing change process. Employees would be one among the key factors of promoting a successful change as well as prohibiting implementation of change. Hence, the mapping of employees’ perception of change needs to be done thoroughly so that a more effective change management can be executed to achieve the targeted change results. Comprehensive perspectives of change implemented in this study by exploring not only the process of managing change and the readiness of change of the employees but also the context of organization in general where the change process exists. Therefore, Organizational Change Questionnaire-Context, Process, Readiness for Change (OCQ-CPR) is given to 21 employees of Foundation X. The results indicate that on average, the employees have negative perception towards the changing circumstances in the organization while they also have neutral perception on the changing process. The study also shows that the employees have mediocre outcome as a result from changes done in the organization. The perception that employees are sometimes taken advantage by their superiors and the thoughts that the change is not beneficial for them are two points that needs to be taken into account by the management so that more positive perception towards organizational context and change outcome can be attained.